Dehalogenation reactions between halide salts and phosphate compounds - Riley, Brian J.; Chong, Saehwa (Frontiers in Chemistry, 2022)
Dehalogenation reactions using phosphate or ammonium hydrogen phosphate reactants [i.e., H3PO4, NH4H2PO4, (NH4)2HPO4] can be used to remove halides from salt-based waste streams, where the process of removing halides yields products that have more efficient disposal pathways for repository storage. In this context, the term efficiency is defined as higher waste loadings and simplified immobilization processes with potential for recycle of certain salt components (e.g., 37Cl as H37Cl or NH437Cl). The main streams identified for these processes are nuclear waste streams generated during electrochemical reprocessing of used nuclear fuel as well as used halide salts from molten salt reactor operation. The potential byproducts of these reactions are fairly consistent across the range of halide species (i.e., F, Cl, Br, I) where the most common are hydrogen halides [e.g., HCl(g)] or ammonium halides (e.g., NH4Cl). However, trihalide compounds are also possible (e.g., NCl3), nitrogen triiodide ammine adducts [NI3·(NH3)x], and ammonium triiodide (NH4I3). Several of these (i.e., NCl3, NBr3, NI3, and NH4I3) are considered to be shock-sensitive contact explosives so their production in these processes must be tracked and carefully controlled, which includes methods of immediate neutralization upon production such as direct transport to and dissolution and decomposition within a caustic scrubber.